Cytokines and chemokines skin gene expression in correlation with immune cells in blood and severity in equine insect bite hypersensitivity - Jebbawi, Fadi; Chemnitzer, Alex; Dietrich, Macsmeila; Pantelyushin, Stanislav; Lam, Juwela; Rhiner, Tanya; Keller, Giulia; Waldern, Nina; Canonica, Fabia; Fettelschoss-Gabriel, Antonia (Frontiers in Immunology, 2024)
Abstract Background: Insect bite hypersensitivity (IBH) is the most frequent skin allergy of horses and is highly debilitating, especially in chronic disease. IBH is caused by IgE mediated hypersensitivity reactions to culicoides midge bites and an imbalanced immune response that reduces the welfare of affected horses. Objective: In the present study, we investigated the pathological mechanisms of IBH aiming to understand the immune cell modulation in acute allergic skin lesions of IBH horses with the goal to find possible biomarkers for a diagnostic approach to monitor treatment success. Methods: By qPCR, we quantified the cytokines, chemokines, and immune receptors gene expression in skin punch biopsies of IBH with different severity and healthy horses simultaneously in tandem with the analysis of immune cell counts in blood. Results: Our data show an increase in blood eosinophils, monocytes and basophils with a concomitant, significant increase in associated cytokine, chemokine and immune cell receptor mRNA expression levels in the lesional skin of IBH horses. Moreover, IL-5Ra, CCR5, IFN- and IL-31Ra were strongly associated with IBH severity, while IL-31, and IL-33 were rather associated with a milder form of IBH. In addition, our data show a strong correlation of basophils cells count in blood with IL-31Ra, IL-5, IL-5Ra, IFN-, HRH2, HRH4, CCR3, CCR5, IL-12b, IL-10, IL-1 and CCL26 mRNA expression in skin punch biopsies of IBH horses. Conclusion: In summary, several cytokines and chemokines have been found to be associated with disease severity, hence contributing to IBH pathology. These molecules can be used as potential biomarkers to monitor the onset and progression of the disease or even to evaluate and monitor efficacy of new therapeutic treatments in IBH skin allergy. To our knowledge, this is the first study that investigate immune cells, together with large set of genes related to their biological function, and including correlation to disease severity in a large cohort of healthy and IBH horses.